The tourism industry and solving the problems of patriotic education for the young generation - Magusovich Safin, Fadbir (2021)
The analysis of the current state and development of social tourism in Russia indicates the need for further research into its content and forms, aimed at introducing the historical and cultural values of our citizens, organizing their active and wholesome recreation, solving the problems of patriotic education for the country's younger generation. The paper discusses some issues of social tourism development in Russia, the role of social tourism in the preservation and development of historical and cultural heritage focuses on the need to develop measures to stimulate tourist demand, strengthen the social component of tourism in the country